Bibliometric mapping of diabetes mellitus and sarcopenia research: hotspots and emerging trends - Wang, Min; Zhou, Qiyang; Guo, Xinyu; Cui, Xiaolong; Tang, Zhongquan; Ou, Ting; Zhao, Xiaomin; Liang, Chen; Xu, Peiyu; Dai, Xinyu; Yao, Jingqing; Ji, Guozhong; et al. (Frontiers in Medicine, 2025)
BackgroundDiabetes mellitus and sarcopenia are chronic metabolic disorders characterized by bidirectional interactions, frequently coexisting as comorbidities whose interrelationship has garnered increasing scientific attention. This study pioneers a bibliometric analysis to systematically investigate their association, aiming to map the knowledge structure, evolutionary trajectories, current foci, and emerging frontiers within this area.MethodsWe retrieved 2,773 publications from the Web of Science Core Collection from inception until December 26, 2024, and visual analyses were conducted using CiteSpace, VOSviewer, R, and Microsoft Excel. The analysis characterized disciplinary distributions, publication outputs, national/regional contributions, institutional collaborations, authorship networks, journal profiles, references, and keywords.ResultsAnnual publications demonstrated sustained growth, with the United States dominating scholarly contributions. Research exhibited marked interdisciplinary integration, although investigations linking type 1 diabetes mellitus with sarcopenia remain limited. Current research hotspots included shared pathological mechanisms such as insulin resistance and chronic inflammation, clinical characterization of specific subtypes such as sarcopenic obesity, imaging-based assessment of muscle dysfunction in diabetes, and the therapeutic efficacy of exercise as an intervention. Mechanistic exploration was determined to be the primary driver of domain advancement.ConclusionThe field has evolved from theoretical frameworks to clinical applications, highlighting the importance of uncovering common pathophysiological mechanisms and pinpointing potential therapeutic targets. Future priorities include refining screening and diagnostic protocols, optimizing preventive strategies, and developing personalized interventions. Cross-disciplinary innovations integrating multi-omics and precision medicine are poised to reshape this research landscape.